Individual, Pair and Group EFL Activities for Aviation Students at a Thai University: A Closer Look at Language Achievement and Attitudes - Thuratham, Wadinlada (LEARN Journal: Language Education and Acquisition Research Network, 2022)
For successful English language communication, EFL students are not only required to have effective language skills for the workplace, but also be able to use the language socially. This study aims to 1) examine student progress in language achievement in the airline context and 2) to investigate student attitudes towards the use of CLT activities in developing English communication skills. The participants were 27 EFL students from one public university in Thailand. The data were collected quantitatively from a language achievement test in the airline context and from a questionnaire. SPSS was used to analyze the data to determine mean scores and standard deviations. The findings from a paired t-test revealed significant differences between the pre-test and the post-test scores at the .05 confidence level. Specifically, the students who engaged in CLT activities had a better understanding of English used in the airline context compared to those who did not, showing marked improvement in vocabulary skills, colloquial language ability and grammatical competency. Furthermore, the results from the questionnaire reflected that students in the study viewed CLT activities (i.e., individual, pair and group activities) as a productive method for developing their English communication skills in the airline context. As a result, students who engage in CLT activities gained a better understanding of English compared to those who did not.